2016
DOI: 10.1038/ni.3444
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β, IL-4 and IL-12 control the fate of group 2 innate lymphoid cells in human airway inflammation in the lungs

Abstract: Group 2 innate lymphoid cells (ILC2s) secrete type 2 cytokines, which protect against parasites but can also contribute to a variety of inflammatory airway diseases. We report here that interleukin 1β (IL-1β) directly activated human ILC2s and that IL-12 induced the conversion of these activated ILC2s into interferon-γ (IFN-γ)-producing ILC1s, which was reversed by IL-4. The plasticity of ILCs was manifested in diseased tissues of patients with severe chronic obstructive pulmonary disease (COPD) or chronic rhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
505
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 402 publications
(539 citation statements)
references
References 46 publications
25
505
3
6
Order By: Relevance
“…Furthermore, our results revealing lower concentration of IL-12 due to curcumin supplementation are in accordance with similar studies (Kang et al, 1999). Together, IL-4, IL-12, IL-1β play an important role in innate lymphocytes in human inflammation (Bal et al, 2016). IL-12 can also stimulate similar functions to IL-2, an essential T-cell proliferation and differentiation factor in the specific immune system (Bachmann and Oxenius, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, our results revealing lower concentration of IL-12 due to curcumin supplementation are in accordance with similar studies (Kang et al, 1999). Together, IL-4, IL-12, IL-1β play an important role in innate lymphocytes in human inflammation (Bal et al, 2016). IL-12 can also stimulate similar functions to IL-2, an essential T-cell proliferation and differentiation factor in the specific immune system (Bachmann and Oxenius, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…35 Human data are scarce, but in mice, IL-17A producing ILC3s were implicated in obesity-induced asthma, 51,52 indicating a possible role for IL-1b 51 as this cytokine can stimulate both ILC2s and ILC3s. 6,53,54 In a pilot study, IL-17A-producing lineage negative cells in BAL were demonstrated to be enriched in patients with severe asthma. 51 So far, no other studies have been performed analyzing ILC subsets in patients with Th2-low asthma.…”
Section: Th2-low Asthmamentioning
confidence: 99%
“…In nonresolving chronic inflammatory Th1-like diseases including Crohn's disease 5 and chronic pulmonary obstructive disease (COPD), the number of ILC1s remains elevated. 6 …”
Section: Ilc1smentioning
confidence: 99%
See 2 more Smart Citations